Nilai-nilai Budaya Sunda Trisilas (Silih Asih, Silih Asah, Silih Asuh) dalam Perspektif Al-Qur’an - Rezqi, Nindy; Furqan, Aulia (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: This study is motivated by the importance of preserving local wisdom to strengthen Islamic values in modern society. Sundanese local wisdom, reflected in the concepts of Silih Asih, Silih Asah, and Silih Asuh, holds moral values that align with the teachings of the Qur'an and can support character formation in society. Objective: The objective of this study is to explore the relationship between the concepts of Sundanese local wisdom, Silih Asih, Silih Asah, and Silih Asuh, and the values found in the Qur'an, highlighting the harmony between them in promoting morality and social ethics. Method: This study uses a descriptive qualitative method with a literature study approach. The researcher collects and analyzes relevant sources to understand the relationship between Sundanese local wisdom and the teachings of the Qur'an. Result: The study's results show that the values in Silih Asih, Silih Asah, and Silih Asuh align with the teachings of the Qur'an. Silih Asih is reflected in Surah Ali-Imran verse 1, Silih Asah in Surah Sad verse 29, and Silih Asuh in Surah Al-Asr verses 1–3. Conclusion: The study concludes that the values of Sundanese local wisdom are in harmony with the moral and spiritual principles of Islam found in the Qur'an. These values can be integrated to strengthen the character formation of society. Contribution: The contribution of this research is to reinforce the integration between local culture and the teachings of the Qur'an, which serves as the foundation for character building, social ethics, and community harmony. This study also highlights the importance of preserving local culture within the Islamic context.